2019
DOI: 10.3390/ma12020222
|View full text |Cite
|
Sign up to set email alerts
|

Microstructures and Isothermal Oxidation of the Alumina Scale Forming Nb1.7Si2.4Ti2.4Al3Hf0.5 and Nb1.3Si2.4Ti2.4Al3.5Hf0.4 Alloys

Abstract: Nb–silicide based alloy will require some kind of coating system. Alumina forming alloys that are chemically compatible with the Nb–silicide based alloy substrate could be components of such systems. The intermetallic alloys Nb1.7Si2.4Ti2.4Al3Hf0.5 and Nb1.3Si2.4Ti2.4Al3.5Hf0.4 were studied in the cast, heat treated and isothermally oxidised conditions at 800 and 1200 °C to find out if they are alumina scale formers. The alloys were designed using the alloy design methodology NICE and were required (i) not to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
92
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 20 publications
(115 citation statements)
references
References 67 publications
(129 reference statements)
4
92
0
Order By: Relevance
“…It is suggested that the formation of these two areas was associated with the strong macrosegregation of Si and Ti in the alloy ZX6 (Table 2). It is worth exploring how areas A and B were formed in the alloy ZX6, because similar transitions have been reported in an alumina scale forming complex concentrated alloy (or high entropy alloy) of the Nb-Ti-Si-Al-Hf system that was prepared using arc melting [25].…”
Section: Nb-24ti-18si-5al-5sn (Alloy Zx6)mentioning
confidence: 78%
See 1 more Smart Citation
“…It is suggested that the formation of these two areas was associated with the strong macrosegregation of Si and Ti in the alloy ZX6 (Table 2). It is worth exploring how areas A and B were formed in the alloy ZX6, because similar transitions have been reported in an alumina scale forming complex concentrated alloy (or high entropy alloy) of the Nb-Ti-Si-Al-Hf system that was prepared using arc melting [25].…”
Section: Nb-24ti-18si-5al-5sn (Alloy Zx6)mentioning
confidence: 78%
“…These relationships are used in the alloy design methodology NICE [14] to design new Nb-silicide based alloys. NICE is also used to design complex concentrated alloys (CCAs) or high entropy alloys [25]. NICE shows that, for oxidation resistance, the trends of VEC and δ are opposite and that alloy design should aim to decrease the former and increase the latter.…”
Section: Alloymentioning
confidence: 99%
“…The presence of Ti 2 Nb 10 O 29 and TiNb 2 O 7 in the scale that formed on Nb-39Ti (at.%) (Nb-25 wt.% Ti) after extended (≥100 h) oxidation between 750 and 780 • C was reported by Felten [70]. The CTE values of oxides in scales of Nb-silicide-based alloys were given in Reference [71]. The Ti 2 Nb 10 O 29 has a negative CTE (−3.1 × 10 −7 / • C) compared with the CTE values of TiNb 2 O 7 (4.5 × 10 −7 / • C) and AlNbO 4 (39.7 × 10 −7 / • C) [72].…”
Section: Oxide Scalesmentioning
confidence: 87%
“…In the introduction we discussed that RMICs, RCCAs and RHEAs intended for application in aero engines would require environmental coatings (ECs) of the BC/TGO/TC type [ 36 , 79 ]. BC Nb-Ti-Si-Al-Hf HEAs forming αAl 2 O 3 TGO [ 80 , 81 ] could be suitable and compatible with Nb-Mo-W-Ti-Cr-Hf-Al-Ge-Si-Sn UHTMs. A good starting point for the design of HEA and/or “conventional” alloys for BC application in ECs could be the (Al/Si) alloy versus [Nb/(Ti + Hf)] alloy maps in Figure 13 in [ 81 ], and the Δχ versus VEC, δ versus VEC and Δχ versus δ maps in Figure 13 in [ 82 ].…”
Section: Summary and Suggestion For Future Workmentioning
confidence: 99%